Mechanics of Brain Tissues Studied by Atomic Force Microscopy: A Perspective - Viji Babu, Prem Kumar; Radmacher, Manfred (Frontiers in Neuroscience, 2019)
Tissue morphology and mechanics are crucial to the regulation of organ function. Investigating the exceptionally complex tissue of the brain at the sub-micron scale turns out to be challenging due to the complex structure and softness of this tissue despite the large interest of biologist, medical engineers, biophysicists and other sin this topic. Atomic Force Microscopy (AFM) both as an imaging and as a mechanical tool provides an excellent opportunity to study soft biological samples such as live brain tissues. Here we review the principles of AFM, the performance of AFM in tissue imaging and me-chanical mapping of cells and tissues, and finally opening the prospects and challenges of probing the biophysical properties of brain tissue using AFM.